Assessment of Atlanto-Axial and Mandibular Rotation by Cone Beam Computed Tomography. Issue 8 (November 2018) - Galli, Massimo; Papini, Andrea; Buffoli, Barbara; Ferrari, Marco; Labanca, Mauro; Rezzani, Rita; Migliario, Mario; Lucchina, Alberta Greco; Rodella, Luigi F.
Abstract : Abstract: The cranial portion of the vertebral segment together with the atlanto-occipital joint represents a very complex area. Since this system could be influenced by different atlas and mandibular position, the aim of this work was to assess atlanto-axial and mandibular rotation. Scanora 3-dimensional cone bean computed tomography images from 205 patients without signs or symptoms of temporomandibular disorder were evaluated. Using a digitalized images analyzer, the axial rotations of atlas and mandible rotation were calculated, measuring the angle with respect to the frontal plane. The same direction for the axial rotation of the mandible and for the atlanto-axial rotation (consistent group) was observed in 80.98% of the patients; opposite directions (inconsistent group) were observed in 19.02%. Among the consistent group, the left rotation was observed in 71.08% of the patients and the right rotation in 28.92%. Absolute values showed a more marked rotation for atlas than mandible and higher values for the left rotation were reported for both. Taking together these data represents important starting points for the knowledge of atlas and mandible relationship and its functional and clinical implication.